Should patients take vitamin D before mandibular operations?. Issue 8 (October 2017) - Syed, N.; Chiu, G.A.; Korczak, P.
Abstract: Vitamin D deficiency is endemic in the United Kingdom (UK), particularly in high-risk groups. We report the outcomes of patients with low concentrations of the vitamin who had complications after reduction of mandibular fractures or osteotomy, and those who were screened preoperatively. A deficiency can be diagnosed with a simple and inexpensive blood test, and in the UK the cost of a vitamin D tablet is about £0.04/tablet/day. Patients at risk of a deficiency should be screened before mandibular operations, and those listed for orthognathic surgery or replacement of the temporomandibular joint should be asked to take a supplement before operation.